STRATEGI DAN TANTANGAN PENERAPAN PENDIDIKAN INKLUSIF DI SEKOLAH DASAR - Sebayang, Gabriela Anjelika; Ginting, Melda Oktika (Universitas Quality, 2025)
The implementation of a companion teacher for children with special needs is an important step in creating an inclusive environment. The companion teacher can help in adjusting teaching, providing individual support, and facilitating social interactions. The importance of effective communication between teachers and the companion teacher, as well as collaboration in planning and implementing learning, also supports the success of this implementation. Overall, the role of the companion teacher can enrich the learning experience of children with special needs.